MENINJAU KEMBALI AYAT-AYAT POLIGAMI: Pendekatan Hermeneutika Muhammad Syahrur dan Implikasinya terhadap Pemahaman Hukum Islam - Kerwanto, Kerwanto; Mesty Sofida, Aeres (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2024)
This study focuses on the study of Muhammad Syahrur's hermeneutics in reading polygamy verses. The background of this study departs from the debate that emerged regarding the interpretation of polygamy verses in the Qur'an, where Syahrur offers a different approach from classical commentators. This study aims to analyze Syahrur's hermeneutic method and explore its implications for understanding the law of polygamy. The method used is qualitative research with a text analysis approach, where Syahrur's works are used as the main source. According to Syahrur, the practice of polygamy can be carried out if there are two limitations: quantitative limitations and qualitative limitations. Polygamy means marrying a single woman without having to be a widow or virgin, according to the understanding of qualitative and quantitative boundary theory. Marrying two or three women means that the widow must have an orphan; The highest limit is four women, and widows must have orphans.